Case report: Remarkable response to a novel combination of mitotane, etoposide, paraplatin, and sintilimab in a patient with metastatic adrenocortical carcinoma - Weng, Yan; Wang, Lin; Wang, Xiao-Yi; Fan, Xin-Xiang; Yan, Li; Li, Zhi-Hua; Zhang, Shao-Ling (Frontiers in Endocrinology, 2023)
Background Adrenocortical carcinoma (ACC) is a rare malignancy with a poor prognosis and limited treatment options for metastases. However, new effective regimens are emerging for specific conditions in metastatic ACC. Case presentation We report a case of a 36-year-old man diagnosed with metastatic ACC who had a large left adrenal mass (158 mm × 112 mm) and multiple metastases in the liver and lungs. Genetic testing revealed a microsatellite instability-high (MSI-H) tumor, a splice mutation in MLH1, and a high tumor mutational burden (TMB). After the left adrenalectomy, he received sequential treatment with a combination of mitotane, etoposide, paraplatin (EP-M), and sintilimab. His condition has been assessed as a stable disease since the sixth cycle of the combined regimen. Conclusion This case highlights the remarkable response of our patient’s ACC with MSI-H tumor, MLH1 spice mutation, and high TMB to treatment with a novel combination of EP-M and sintilimab. Our findings suggest a promising therapeutic option for patients with similar molecular profiles.